2005
DOI: 10.2514/1.8092
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Application of an Active Control Loop on Backward-Facing Step Flow.

Abstract: Experimental results are presented on the active control of a backward-facing step flow revealing some features observed in combustion chambers. These experiments were performed under nonreactive conditions, and the effect of the pressure fluctuations induced by the unsteady heat release was simulated by an external acoustic excitation produced by two loudspeakers placed far downstream from the step. This excitation signal was delivered by a generator or by a hot-wire probe placed in the shear layer. The latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…With this background, the rest of this section reviews studies that have analyzed the forced response of flows to transverse (or non-axisymmetric) forcing. Studies of shear layer instability and forced response include forcing the flow from the upstream plenum [224,225], by mechanical actuation [226,227], or transversely deflecting the shear layer [228][229][230][231][232][233][234]. For example, Fiedler and Mensing [233] forced the shear layer transversely by exciting a waveguide that opened at a slit at the separation point of the mixing layer.…”
Section: Transverse Forcing Of Typical Combustor Flow Fieldsmentioning
confidence: 99%
“…With this background, the rest of this section reviews studies that have analyzed the forced response of flows to transverse (or non-axisymmetric) forcing. Studies of shear layer instability and forced response include forcing the flow from the upstream plenum [224,225], by mechanical actuation [226,227], or transversely deflecting the shear layer [228][229][230][231][232][233][234]. For example, Fiedler and Mensing [233] forced the shear layer transversely by exciting a waveguide that opened at a slit at the separation point of the mixing layer.…”
Section: Transverse Forcing Of Typical Combustor Flow Fieldsmentioning
confidence: 99%
“…For a BFS whose separating boundary layer has 3-D flow fluctuations at sufficiently high Reynolds number, the wake flow exhibits global instability and is an "oscillator" flow; most previous studies agree on the existence of a shedding/step mode and a lower frequency flapping or bubble pumping mode [13][14][15]. Previous numerical [15,16] and experimental [8,[17][18][19] feedback control studies have been performed; with the exception of [15], the sensor signal has been either based on wake velocity measurements or a measure of the reattachment length.…”
mentioning
confidence: 99%
“…The step mode based on the step height h, and defined by Strouhal number, S rh = f h U ⁄ characterizes the second instability mode. He observed these values to be around Srθ = 0.012 and Srh = 0.185 respectively, these values match with the values obtained lately by Marrot et al (2005), Sth =0.14 and Dejoan et al (2005), Sth =0.2. In Vukasinovic et al ( 2010), active flow control in a backwards facing step under turbulent conditions was studied, it was reported that a slight waviness of energy in the boundary layer results in a low scale periodic vortex train.…”
Section: Introductionsupporting
confidence: 86%
“…When studying boundary layer performance in low-pressure turbines with AFC, Sondergaad et al (2002) and , observed that unsteady suction was more effective that steady one, and AFC jets located perpendicular to the surface were more effective than tangential ones. Marrot et al (2005) used a loudspeaker located downstream of the step to activate the boundary layer, the maximum effect was observed when the loudspeaker frequency was equal to the boundary layer instability mode, at these conditions a small reduction of the recirculation length was obtained. The pre-excited flow was controlled using two rows of synthetic jets located on the vertical side of the step.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation